Implementing a community-based caregiver intervention in limited-resource settings: a focus on implementation strategies - Combrinck, Jeanri (Department of Psychiatry and Mental Health, 2023)
The systematic use of implementation strategies can enhance sustainable implementation of evidence-based interventions in real-world settings. However, there are little data on the use of implementation strategies in low-resourced settings. The World Health Organization Caregiver Skills Training Programme (WHO-CST) for families of children with developmental disabilities was piloted in a rural setting in South Africa and was called the 'Diamond Families Project'. The goal of this study was to describe systematically the implementation strategies used during the planning phase of the project. Archival project records were reviewed to identify all planning activities, which were coded into implementation strategies using a tailored manual and consensus coding approach. We identified 150 activities representing 33 unique implementation strategies across nine categories. Developing stakeholder interrelationships was the most frequently used category, with the largest number of actors, highest costs, and longest cumulative duration. Developing an implementation blueprint was the most frequently used individual strategy, while promoting adaptability had the longest duration. The Diamond Families Project incorporated a comprehensive set of implementation strategies with a clear focus on building stakeholder relationships. Findings contribute to an evidence-base of implementation strategies for WHO-CST in South Africa, which may inform the implementation of interventions in similar low-resourced settings.